Dynamic coupling between transportation networks and urban vitality in the Lanzhou–Xining urban agglomeration - Yang, Minan; Qian, Yongsheng; Li, Xin; Liu, Zhen; Zeng, Junwei (Frontiers in Earth Science, 2024)
This study is grounded in the coordinated development of the "transportation-urban vitality" coupling in county-level spaces within urban agglomerations. The research object is the Lanzhou-Xining urban agglomeration, a typical western region of China. The interactive relationship between the transportation network of county-level cities within the urban agglomeration and urban vitality is selected, and the vitality evaluation model and spatial syntax model are used to measure the functional vitality, socio-economic vitality, and transportation network accessibility of the urban agglomeration. On this basis, the evolution characteristics of the coupling coordination level between the transportation network and the urban vitality of the Lanzhou-Xining urban agglomeration. The research found that over the past decade, the transportation network accessibility of the Lanzhou-Xining urban agglomeration and the vitality of the nodal cities have significantly increased. However, the internal development of the urban agglomeration needs to be more balanced. The dual-coredriven urban agglomeration has formed a distinct "ridge line" connection, but the polarization phenomenon caused by the "core-periphery" structure is still prominent. The coupling coordination level of spatial development in the county-level space of the Lanzhou-Xining urban agglomeration varies greatly, with about 80% of the county-level cities still in a state of imbalance, leading to a mismatch between the transportation network and urban vitality of the Lanzhou-Xining urban agglomeration. This research result is worth deep reflection by city managers and participants on the development path of urban agglomerations formed by "weak-weak" alliances.